Surgical Explantation of an Amplatzer Device for Patent Foramen Ovale Closure in a Patient With Nickel Allergy: A Case Report - Ujjawal Kumar; Usman Aslam; Anthony Cooper; Zain Khalpey (Clinical Case Reports)
ABSTRACT Patent foramen ovale (PFO) closure using percutaneous devices, such as the Amplatzer occluder, is a common treatment for patients with a history of cryptogenic stroke or transient ischemic attack (TIA). Although generally well‐tolerated, some patients may develop adverse reactions to the device materials, particularly in the presence of a nickel allergy. Symptoms can include chest pain, rashes, and migraines, which may necessitate surgical removal of the device. In such cases, careful surgical planning and execution are essential to ensure successful outcomes and symptom resolution. We present the case of a 39‐year‐old female with existing PFO closure using an Amplatzer device, who developed severe, persistent atypical chest pain radiating to her upper extremities and occasional migraines 1 month after Amplatzer implantation. Patch testing confirmed a nickel allergy, prompting a referral to our service for surgical explantation of the device. The patient underwent Amplatzer device removal and reconstruction of the interatrial septum via sternotomy. The surgical technique involved meticulous excision of the device while preserving maximal septal tissue, allowing for primary closure of the interatrial septum without the need for a pericardial patch. Intraoperatively, significant scar tissue and inflammation were observed surrounding the device and atrial septal tissue, necessitating careful excision while preserving healthy tissue. The left atrial appendage was oversewn using a polypropylene suture for thromboembolism prophylaxis. Amniotic membrane allograft and autologous platelet‐rich plasma were applied to promote wound healing, with specialized suture tapes used for chest closure to avoid using stainless steel sternal wires (the most common alloy, 316 L surgical steel contains around 15% nickel) and minimize the risk of sternal complications. The patient tolerated the procedure well, with complete resolution of symptoms following device removal. At follow‐up, she reported improved exercise tolerance, enhanced quality of life, and was able to discontinue her pregabalin medication after 30 months of use (600 mg once daily). She returned to work with light duties 6 weeks postoperatively. This case highlights the importance of preoperative allergy testing to consider nickel allergy in patients before implanting devices such as an Amplatzer, as well as after considering de novo nickel sensitization as a potential cause when such symptoms develop after implantation. This case also highlights the value of surgical intervention in alleviating symptoms and optimizing patient outcomes in cases of device‐related complications.